Implementasi Front-End Development Menggunakan Next.js Dalam Mendukung Aktivitas Akademik Dosen - Refin Dhani Eka Purnama; Weda Adistianaya Dewa (Sekolah Tinggi Manajemen Informatika & Komputer PPKIA Pradya Paramita Malang, 2026)
The Academic Information System (SIAKAD) plays an important role in supporting academic activities in higher education institutions. This study applies front-end development using the Next.js framework to replace the previous Angular 10-based system, which faced performance and maintenance issues. The development process follows an iterative Agile approach, including requirement planning, use case diagram preparation for both lecturers and students, interface implementation, API integration, testing, deployment, and maintenance. The implementation results show that the system enables lecturers to validate KRS, review academic results, manage attendance, and access transcript copies, while students can fill out KRS, view KHS, monitor CPL/CPMK, and manage personal data. Blackbox testing confirmed that all features function as expected. The use of Next.js offers advantages in rendering performance, modular component development, and API integration efficiency, making the system optimal, maintainable, and ready for future development.